Islamic Educational Values in the Baritan Tradition in Maron Village Garung District Wonosobo Regency - Moh. Amin; Robingun Suyud El Syam (International Journal Labs, 2025)
Indonesia’s pluralistic society faces cultural erosion due to globalization, necessitating the preservation of local traditions infused with religious values. The Baritan tradition in Maron Village, Wonosobo, exemplifies Javanese-Islamic syncretism, yet its Islamic educational dimensions remain underexplored. This study aims to uncover the Islamic educational values within Baritan, framing it as a tool for spiritual and communal resilience. A qualitative phenomenological approach was employed, with data collected through observation, interviews, and documentation, analyzed to reveal deeper meanings beyond generalizations. Baritan embodies Islamic values—gratitude, disaster prevention, kinship, mutual cooperation, and ecological spirituality—serving as a conduit for personal, social, and ecological piety. Its rituals (e.g., Wedus Kendit sacrifice, communal feasts) reinforce divine-centric worship and environmental stewardship. The study advocates integrating Baritan’s values into Islamic education curricula to counteract cultural degradation. Future research should explore its role in sustainable development and intergenerational transmission.